What Is the Nature of Hedge Fund Manager Skills? Evidence from the Risk-Arbitrage Strategy. (29th July 2016) - Cao, Charles; Goldie, Bradley A.; Liang, Bing; Petrasek, Lubomir
Abstract: To understand the nature of hedge fund managers' skills, we study the implementation of risk arbitrage by hedge funds using their portfolio holdings and comparing them with those of other institutional arbitrageurs. We find that hedge funds significantly outperform a naive risk-arbitrage portfolio by 3.7% annually on a risk-adjusted basis, whereas non–hedge fund arbitrageurs fail to outperform the benchmark. Our analysis reveals that hedge funds' superior performance does not reflect fund managers' ability to predict or affect the outcome of merger and acquisition deals; rather, hedge fund managers' superior performance is attributed to their ability to manage downside risk.